OP0300 Do Depressive Symptoms at Disease Onset Associate with Future Disease Activity for Adolescent Patients with Jia? Results from The Childhood Arthritis Prospective Study (CAPS). (15th July 2016) - Hanns, L.; Cordingley, L.; Galloway, J.; Norton, S.; Carvalho, L.A.; Christie, D.; Sen, D.; Carrasco, R.; Rashid, A.; Foster, H.; Baildam, E.; Cheing, A.; et al.
Abstract : Background: Adolescents with rheumatic disease have a four times higher incidence of depression than healthy peers. Studies in adults have shown an association between depression and worse disease in rheumatoid arthritis, yet this association has never been explored in detail for patients with JIA or in a purely adolescent population. Objectives: This study investigates the association between depressive symptoms and 1) disease activity at onset and 2) future disease activity. Methods: Data are from JIA patients in the Childhood Arthritis Prospective Study, a nationwide inception cohort of childhood onset arthritis. Patients are recruited within 6 months of disease onset and the first study visit is identified as "baseline". Patients were included in this analysis if they were aged 11–16 at baseline. Depressive symptoms were assessed using the Mood and Feelings Questionnaire (MFQ). Associations at baseline were analysed using Spearman's correlation. Separate piecewise linear mixed-effect models for change in active joint count and disability (Childhood Health Assessment Questionnaire (CHAQ)) over 48 months was estimated. A change point at 12 months allowed for different rates of change between 0–12 months and 12–48 months. MFQ score at baseline was included as a covariate Results: 102 patients were included. At baseline, mean age was 12.7 years (SD1.4) and 15.7% were taking DMARDS. 56.7% were female, 52.0% had persistent oligoarticular arthritis, 30.4% had polyarticular arthritis and 17.6% had enthesitis related arthritis. 14.7% scored over the MFQ cut-off for probable depression (>27) at baseline. At baseline, depressive symptoms significantly associated with disability (r=0.51, p<0.000) and active joint count (r=0.32, p=0.001). Longitudinal analysis showed that depressive symptoms, active joint count and disability rapidly decreased during the first 12 months after baseline and then stabilised. After 12 months, baseline depressive symptoms no longer associated with active joint count whereas disability for those with high baseline depressive symptoms continued to be higher than those with low depressive symptoms (Figure 1 ). Conclusions: At disease onset, 14.7% adolescents with JIA have significant depressive symptoms. Those with more depressive symptoms have higher numbers of inflamed joints and more disability. In the 12 months after disease onset, a reduction in disease activity is mirrored by improvements in mental health. After the first year, baseline depression no longer associates with subsequent disease activity but remains associated with higher disability. This highlights the importance of psychological health assessment for adolescent patients with JIA and underlines the need for psychological support fully integrated into their routine care. Disclosure of Interest: None declared